Uz Linux balstīta slodzes līdzsvarošana HAProxy un Nginx augstas pieejamības tīmekļa pakalpojumiem - Sokolov, Mark (Latvijas Universitāte, 2025)
This bachelor paper examines the importance of how to and why we should know Linux-based load balancing. In recent years, cloud computing has become dominant in the modern world. Small businesses migrate to the cloud as soon as more and more customers of their service reach out via the web. By hitting one resource on the web, more load on a server is persisting. At a certain point, the server may become overloaded and fail. To address this issue, the business can deploy another server to handle increased load. Here the main question arises, how to distribute traffic between two servers? How could requests of users be effectively balanced across multiple servers? What modern tools are available to solve this problem? As soon as business grows, traffic to the service grows, therefore, the business is going to add more servers to handle connections. The primary goal is to simulate a high load web service and use existing load balancing tools and try to have best practices to achieve it
Linux-Based Load Balancing HAProxy and Nginx for High-Availability Web Services
Keywords: Datorzinātne; Linux; load balancer; web; services